Moral philosophy Abaya as a testament to the generations (Journal of Philosophy Culture and Political Science, 2018)
The article reveals the spiritual and moral philosophy of Abay as the Foundation, ideological and theoretical source of modern Kazakh culture. The analysis of the main provisions of his teaching, which incorporated the moral values of world spirituality, especially Russian, is carried out. It is shown that in addition to Russian culture, the process of formation and development of Abay’s teachings was influenced by the culture of three world cultures – Western (European), Eastern (Buddhism, Islam) and Turkic (Kazakh). On the basis of the analysis of the research literature reveals the categorical apparatus of Abay’s teachings, the initial beginning of which is the nature in which God is dissolved (Allah). This is a kind of pantheism. The essential basis of it is the understanding of man as a microcosm, which acts as a holistic, universal being. And this integrity he gets through the unity of body and soul. When this unity is destroyed, the end of life comes. Eternal, imperishable in man remains his soul, spirit. Therefore, Abay made high demands on the person, calling him to be a Man (Adam bol). The spiritual and moral teaching of the thinker, consonant with our time, is studied in detail.Key words: Abay’s philosophy, Sufism, theoretical sources, «words of edification», ontology, epistemology, morality, «Adam bol», universalism.